2020
DOI: 10.1016/j.jaccas.2020.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Wandering Atrial Pacemaker Wire

Abstract: Temporary epicardial pacing, routinely used after cardiac surgery, employs wires anchored to the epicardium allowing removal via traction. In cases of resistance, the temporary wires are cut flush at the skin. We present a rare noninfectious case of a migrated retained temporary pacing wire into the left heart. ( Level of Difficulty: Beginner. )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…TEPWs are commonly used in open-heart surgery and manually removed when no longer required. However, the lead is often cut at the skin entrance site to prevent myocardial damage or CABG graft injury if there is resistance during wire removal [ 1 - 3 ]. Residual TEPW migration has been reported in the right heart system, as reported in this case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TEPWs are commonly used in open-heart surgery and manually removed when no longer required. However, the lead is often cut at the skin entrance site to prevent myocardial damage or CABG graft injury if there is resistance during wire removal [ 1 - 3 ]. Residual TEPW migration has been reported in the right heart system, as reported in this case.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the removal of the residual TEPW using a snare catheter is effective [ 3 , 5 , 8 , 9 ]. Some cases require reopening of the chest and extracorporeal circulation to remove the residual TEPW [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TEPW was removed at this time. It is unclear what caused the migration of TEPW but multiple accounts in the literature have described the incidental migration into cardiac and vascular structures [ 5 ]. Previously described cases of TEPW transaortic migration were managed conservatively with antithrombic/anticoagulation medications and close follow-up [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…From our limited experience, cases of TEPW migration need to be addressed on an individual basis and it would be difficult to recommend removal in all cases with cardiac re-operation having significant risks of morbidity and mortality. Additionally, some wires may be removed with endovascular approaches [ 5 ]. In the case presented, the patient had additional indications for a re-operation.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature several cases of migrating retained pacing wires have been reported: some migrated into the aortic arch [4], others into abdominal aortic aneurysms [5] and the left heart [6]. There are also case reports of accidental encounter of TEPWs during elective colonoscopy [7], stomach migration causing dyspepsia [8] and wires exiting from the jaw of a patient [9,10]. Sometimes the retrieval is by accident; other times the retention and migration can lead to more serious consequences, as in the clinical case reported by Horng et al [11], in which the retained wires migrated to the upper lobe of the right lung of the patient, causing severe dyspnea.…”
Section: Retention Of Temporary Epicardial Pacing Wires: When Migrati...mentioning
confidence: 99%